Epidemiology of congenital heart diseases in Bogotá, Colombia, from 2001 to 2014 : improved surveillance or increased prevalence? (2018)
Introduction: Congenital heart diseases are functional and structural alterations of the heart, circulatory system, and large vessels, which develop during cardiac embryogenesis. These defects are significant causes of morbidity and mortality in children